Hybridization of β-Adrenergic Agonists and Antagonists Confers G Protein Bias - Stanek, Markus; Picard, Louis Philippe; Schmidt, Maximilian; Kaindl, Jonas; Hübner, Harald; Bouvier, Michel; Weikert, Dorothée; Gmeiner, Peter (Journal of Medicinal Chemistry, 2019)
Starting from the β-adrenoceptor agonist isoprenaline and beta-blocker carvedilol, we designed and synthesized three different chemotypes of agonist/antagonist hybrids. Investigations of ligand-mediated receptor activation using bioluminescence resonance energy transfer biosensors revealed a predominant effect of the aromatic head group on the intrinsic activity of our ligands, as ligands with a carvedilol head group were devoid of agonistic activity. Ligands composed of a catechol head group and an antagonist-like oxypropylene spacer possess significant intrinsic activity for the activation of Gα s , while they only show weak or even no β-arrestin-2 recruitment at both β 1 - and β 2 -AR. Molecular dynamics simulations suggest that the difference in G protein efficacy and β-arrestin recruitment of the hybrid (S)-22, the full agonist epinephrine, and the β 2 -selective, G protein-biased partial agonist salmeterol depends on specific hydrogen bonding between Ser 5.46 and Asn 6.55 , and the aromatic head group of the ligands.
CRIS-Team Scopus Importer:2019-06-04